Selinunt, Italien. Forschungen in Selinunt, Teil 1. Ein neues Modell für die Stadt Selinunt. Die Feldarbeiten des Jahres 2021 - Jonasch, Melanie; Adorno, Linda; Burgio, Aurelio; Di Maggio, Antonio; Harms, Morten; Schlöffel, Marlen; Schneider, Steffen; Wilken, Dennis (e-Forschungsberichte des DAI, 2022)
Since 2021, the German Research Foundation has been funding a new interdisciplinary field project to investigate the urban fabric of the Greek colony of Selinous in a spatially comprehensive and diachronic perspective. The project aims at extending the existing model of the ideal Greek city by considering also the historically conditioned fractures in the urban development and the multiple transformations of the living space between the 7th and 3rd century BCE. This is to be pursued by large scale archaeological, geophysical and geoarchaeological prospections, small excavations in selected areas and the thorough study of the finds and archaeobiological remains. This is a report about the first field campaigns of the various specialist disciplines and a presentation of some preliminary results.